Computer Aided System of Time Series Analysis Methods for Forecasting the Epidemics Outbreaks - Polyvianna, Yulia; Chumachenko, Dmytro; Chumachenko, Tetyana (My University, 2019)
The research is devoted to the problem of predicting the incidence of gastroenterocollitis. The paper discusses the forecasting of time series by statistical models. The methods of exponential smoothing and adaptive exponential smoothing are proposed, applied to additive and multiplicative time series models. The analysis of the results obtained using the developed computer aided system.
Keywords: forecasting of time series; forecasting the epidemic process; method of exponential smoothing; brown polynomial model; adaptive Holt method